2004
DOI: 10.1002/jcp.20169
|View full text |Cite
|
Sign up to set email alerts
|

Mitogen‐activated protein kinases and asthma

Abstract: Mitogen-activated protein kinases (MAPKs) are evolutionary conserved enzymes which play a key role in signal transduction mediated by cytokines, growth factors, neurotransmitters and various types of environmental stresses. In the airways, these extracellular stimuli elicit complex inflammatory and structural changes leading to the typical features of asthma including T cell activation, eosinophil and mast cell infiltration, as well as bronchial hyperresponsiveness and airway remodelling. Because MAPKs represe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
66
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(72 citation statements)
references
References 134 publications
4
66
0
2
Order By: Relevance
“…These findings were confirmed by stimulating the cells with nucleotides in the presence of SB-203580, a specific p38 MAPK inhibitor. It is known that p38 MAPK can phosphorylate numerous downstream substrates, including heat shock protein (HSP27), transcription factors ATF2/6, Chop, Max, MEF2C, nuclear histone H3, or other kinases, such as PRAK (p38-regulated/activated protein kinase), MNK1/2 (MAPK-interacting kinase 1/2), MSK1 (mitogen-and stressactivated kinase 1), and MAPK-activated protein kinase 2 (MAPKAP-K2) (51). It has also been reported that p38 MAPK-dependent synthesis of cytokines, including IL-6, involves MAPKAP-K2.…”
Section: Discussionmentioning
confidence: 99%
“…These findings were confirmed by stimulating the cells with nucleotides in the presence of SB-203580, a specific p38 MAPK inhibitor. It is known that p38 MAPK can phosphorylate numerous downstream substrates, including heat shock protein (HSP27), transcription factors ATF2/6, Chop, Max, MEF2C, nuclear histone H3, or other kinases, such as PRAK (p38-regulated/activated protein kinase), MNK1/2 (MAPK-interacting kinase 1/2), MSK1 (mitogen-and stressactivated kinase 1), and MAPK-activated protein kinase 2 (MAPKAP-K2) (51). It has also been reported that p38 MAPK-dependent synthesis of cytokines, including IL-6, involves MAPKAP-K2.…”
Section: Discussionmentioning
confidence: 99%
“…1d). Since this pathway is undoubtedly activated in asthma and chronic obstructive pulmonary disease and may contribute to the inflammation and even remodelling of the airway wall [168], it is tempting to speculate that further activation of ERK-dependent signalling may account for some of the adverse clinical observations made with b 2 -adrenoceptor agonists described above [169,170]. Such effects, as are often the case, require appropriate validation in primary cells relevant to the airways or suitable animal models.…”
Section: Promiscuous G-protein Couplingmentioning
confidence: 99%
“…These pro-inflammatory cytokines and chemokines, together with IL-1b, strongly activate the p38 subgroup of mitogen-activated protein kinases (MAPKs), a family of signal transduction enzymes that also include extracellular signal-regulated kinases (ERK) and c-jun NH 2 -terminal kinases (JNK) [4]. MAPKs are organised hierarchically into three modules, operating via a phosphorylation cascade that converts them into activated forms, thereby enabling their interaction with cytoplasmic substrates and translocation to the nucleus, where many MAPK targets, such as transcription factors and histones, are located [5]. The ERK pathway is stimulated in particular by G-protein coupled receptors and growth factors involved in cell proliferation, differentiation and survival, whereas JNK and p38 modules are activated mainly by cytokines implicated in inflammation and apoptosis [6].…”
mentioning
confidence: 99%